2019
DOI: 10.1111/1758-2229.12728
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial compositions mirror caste‐specific diets in a major lineage of social insects

Abstract: SummarySocial insects owe their ecological success to the division of labour between castes, but associations between microbial community compositions and castes with different tasks and diets have not been extensively explored. Fungus‐growing termites associate with fungi to degrade plant material, complemented by diverse gut microbial communities. Here, we explore whether division of labour and accompanying dietary differences between fungus‐growing termite castes are linked to gut bacterial community struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 43 publications
7
56
1
Order By: Relevance
“…Similarly, we predict that the structure and function of worker and reproductive gut microbiomes diverge during colony growth (Figure 2). The gut microbiomes of termite reproductives indicate a transition from diverse to simplified communities from founding to maturity (Shimada et al, 2013;Benjamino and Graf, 2016;Inagaki and Matsuura, 2016;Diouf et al, 2018;Otani et al, 2019) (Figure 2), which has been suggested to be a consequence of specialization on reproduction and dependence on workers (Chouvenc and Su, 2017). Similarly, the gut microbiome of honey bee queens exhibits slight changes with age (Tarpy et al, 2015;Anderson et al, 2018), suggesting that physiological and dietary changes related to reproductive specialization and duration may influence gradual shifts the reproductive microbiota.…”
Section: Colony and Microbiota Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, we predict that the structure and function of worker and reproductive gut microbiomes diverge during colony growth (Figure 2). The gut microbiomes of termite reproductives indicate a transition from diverse to simplified communities from founding to maturity (Shimada et al, 2013;Benjamino and Graf, 2016;Inagaki and Matsuura, 2016;Diouf et al, 2018;Otani et al, 2019) (Figure 2), which has been suggested to be a consequence of specialization on reproduction and dependence on workers (Chouvenc and Su, 2017). Similarly, the gut microbiome of honey bee queens exhibits slight changes with age (Tarpy et al, 2015;Anderson et al, 2018), suggesting that physiological and dietary changes related to reproductive specialization and duration may influence gradual shifts the reproductive microbiota.…”
Section: Colony and Microbiota Developmentmentioning
confidence: 97%
“…In some social insect clades, the reproductive caste microbiome is distinct and drastically simplified compared to that of the worker caste. Foraging lower termite reproductives generally lack symbiotic protists that dominate the worker guts (Shimada et al, 2013;Inagaki and Matsuura, 2016), and the reproductive caste of Termitidae termites shows reduced diversity and disparate bacterial community composition (Otani et al, 2019) compared to the worker caste (Dietrich et al, 2014;Otani et al, 2014Otani et al, , 2016Otani et al, , 2019. Honey bee queens also host a simplified bacterial community that is significantly reduced compared to workers (Kapheim et al, 2015;Tarpy et al, 2015;Anderson et al, 2018).…”
Section: Current Knowledge On Caste-distinct Gut Microbiomesmentioning
confidence: 99%
See 1 more Smart Citation
“…These unicellular eukaryotes can reach population sizes of 10 5 per host individual, representing 60% of total hindgut weight (Bignell, 2011;Brune, 2011). Nonetheless, the literature on host-microbiome interaction in insects in general and termites in particular is based primarily on their bacterial and fungal symbionts (e.g., Aanen et al, 2002;Engel and Moran, 2013;Mikaelyan et al, 2015aMikaelyan et al, , 2017aGraf, 2016;Diouf et al, 2018;Otani et al, 2019). This is partly because the mutualistic partnership with flagellates appears unique among insects, but also because of methodological difficulties.…”
Section: The Hindgut Microbiomementioning
confidence: 99%
“…However, the defined social structures of eusocial insects may be useful for understanding and manipulating microbial transmission later in life. Reproductive queens have limited contact with other adult workers, for instance, and understanding when and how they share microbes with other castes could illuminate the social elements of microbial transmission (Otani et al, 2019). Microbiomes of distinct nest structures provide an interesting comparison to the idea of built environments (Sharma and Gilbert, 2018).…”
Section: What Can We Learn From Insects?mentioning
confidence: 99%